Stability Criteria for Impulsive Stochastic Functional Differential Systems With Distributed-Delay Dependent Impulsive Effects - Hu, Wei; Zhu, Quanxin (IEEE transactions on systems, man, and cybernetics. Systems, 2021)
In this short note, we consider time-varying stochastic functional differential systems with distributed-delay dependent impulsive effects. Such systems arise from a large number of applications, such as financial markets and population dynamics. By developing some inequality techniques and then combining stochastic analysis theory, Lyapunov approach, some stability criteria for such systems are established. The feature of the criteria shows that derivatives of the Razumikhin functions are allowed to be indefinite, and the restrictions with respect to the system parameters is very loose. Finally, we carry out two numerical experiments to show the usefulness and significance of the criteria.